A novel method for evaluating the dynamic biocompatibility of degradable biomaterials based on real-time cell analysis. Issue 3 (1st May 2020) - Gai, Xiaoxiao; Liu, Chenghu; Wang, Guowei; Qin, Yang; Fan, Chunguang; Liu, Jia; Shi, Yanping
Abstract: Degradable biomaterials have emerged as a promising type of medical materials because of their unique advantages of biocompatibility, biodegradability and biosafety. Owing to their bioabsorbable and biocompatible properties, magnesium-based biomaterials are considered as ideal degradable medical implants. However, the rapid corrosion of magnesium-based materials not only limits their clinical application but also necessitates a more specific biological evaluation system and biosafety standard. In this study, extracts of pure Mg and its calcium alloy were prepared using different media based on ISO 10993:12; the Mg 2+ concentration and osmolality of each extract were measured. The biocompatibility was investigated using the MTT assay and xCELLigence real-time cell analysis (RTCA). Cytotoxicity tests were conducted with L929, MG-63 and human umbilical vein endothelial cell lines. The results of the RTCA highly matched with those of the MTT assay and revealed the different dynamic modes of the cytotoxic process, which are related to the differences in the tested cell lines, Mg-based materials and dilution rates of extracts. This study provides an insight on the biocompatibility of biodegradable materials from the perspective of cytotoxic dynamics and suggests the applicability of RTCA for the cytotoxic evaluation of degradable biomaterials.